Aortic valve laceration following coronary angiography and percutaneous coronary intervention. Issue 11 (12th September 2016) - Roy, James; Manganas, Con; Youssef, George; Rees, David
Abstract: Valve complications following coronary angiography and percutaneous coronary interventions are rare. We report a case of an aortic valve laceration following cardiac catheterization and percutaneous coronary intervention, which required surgical valve replacement.